Fish assemblages in the Southern California Current: relationships with climate, 1951–2008. (4th February 2013) - Anthony Koslow, J.; Goericke, Ralf; Watson, William
Abstract We examined the dominant patterns of variability in the fish fauna of the southern California Current based on a principal component (PC) analysis of the California Cooperative Oceanic Fisheries Investigations ichthyoplankton data set, 1951–2008. Eighty‐six taxa were analyzed, including all ecologically dominant fish species, both exploited and unexploited. The first three PCs accounted for 20.5, 12.4 and 6.8% of the variance of the data, respectively (total: 39.7%). Each was dominated by taxa from particular adult or larval habitats. PC 1 predominantly represented the coherent response of 24 mesopelagic taxa from 10 families and was most highly correlated with long‐term trends in midwater oxygen levels. PC 2 was dominated by six of the seven most abundant ichthyoplankton taxa in the region, predominantly California Current endemics including key pelagic species (northern anchovy, Pacific sardine and Pacific hake), rockfishes (genus Sebastes) and two midwater taxa. It was correlated primarily with sea surface temperature and exhibited a significant declining trend. PC 3 was dominated by coastal and reef‐associated fishes with predominantly southerly affinities. It was positively correlated with sea surface temperature and sea level height, a proxy for diminished flow of the California Current. The taxa dominating PCs 2 and 3 mostly spatially co‐occur as ichthyoplankton. These results suggest that fish assemblages in the California Current are predominantly influenced by environmental forcing of their ocean habitats as adults or larvae, or both.